2015
DOI: 10.1017/ice.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment of Asymptomatic Bacteriuria: Identifying Targets for Improvement

Abstract: Treatment of asymptomatic bacteriuria contributes to antimicrobial overuse in hospitalized patients. Indications for urine culture, treatment, and targets for improvement were evaluated in 153 patients. Drivers of antimicrobial overuse included fever with an alternative source, altered mental status, and leukocytosis, which led 435 excess days of antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…Positive urine cultures are a powerful behavioral stimulus for treatment with antibiotics regardless of medical appropriateness. 9,10 Our findings provide 2 important contributions to the literature. First, the association of urine culture testing on antibiotic use was greatest for patients admitted through the emergency room.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Positive urine cultures are a powerful behavioral stimulus for treatment with antibiotics regardless of medical appropriateness. 9,10 Our findings provide 2 important contributions to the literature. First, the association of urine culture testing on antibiotic use was greatest for patients admitted through the emergency room.…”
Section: Discussionmentioning
confidence: 69%
“…Recent studies have demonstrated that 61%-71% of positive urine cultures in hospitalized patients represent asymptomatic bacteriuria. 9,10 Prior literature has routinely demonstrated that hospitalized patients are often inappropriately started and continued on antibiotics in response to false-positive urine cultures. [7][8][9][10] Unnecessary antibiotics have risks, not only for the patients receiving the antibiotics but also for other patients cared for in the same hospital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations